Regulation of Serum Sodium Levels during Chemotherapy Using Selective Arginine Vasopressin V2-Receptor Antagonist Tolvaptan in a Four-Year-Old Girl with a Suprasellar Germ Cell Tumor - Shota Hiroshima; Hiromi Nyuzuki; Sunao Sasaki; Yohei Ogawa; Keisuke Nagasaki (MDPI AG, 2021)
There are limited reports on the use of tolvaptan for syndrome of inappropriate antidiuretic hormone secretion (SIADH) in children. Managing serum sodium levels in SIADH patients during chemotherapy is often difficult because of the need for massive fluid infusions. We report the course of the use of tolvaptan for the treatment of hyponatremia during chemotherapy in a four-year-old girl with a suprasellar germ cell tumor. The patient was a Japanese girl who presented with left ptosis with a mass in the pituitary gland and cavernous sinus. She was diagnosed with an intermediate-grade germ cell tumor and was treated with carboplatin and etoposide combination chemotherapy. She developed hyponatremia due to SIADH caused by intravenous infusion therapy before chemotherapy. Subsequently, tolvaptan (3.25 mg; 0.20 mg/kg/dose) was administered orally to control serum sodium levels. After 4 h of administration, a marked increase in urine volume of up to 15 mL/kg/h was observed, and serum sodium level increased from 126 to 138 mEq/L after 10 h of tolvaptan administration, followed by a decrease in urine volume. The use of tolvaptan in pediatric patients with SIADH who require intravenous hydration during chemotherapy can be useful for the management of serum sodium balance.